Coalitions and the organization of multiple-stakeholder action: a case study of agricultural research and extension in Rajasthan, India - Alsop, Ruth (International Food Policy Research Institute, 1998)
Decentralization implies an increase in the number of stakeholders involved in the design and implementation of interventions. This paper draws upon the experience of a multi-stakeholder program in India which has sought to increase the contribution of rainfed agriculture to rural household's economic portfolios. The strategy has been one of enhancing government research and extension service provision through collaboration and coalition building between NGOs and government line departments. Evidence from the last four years demonstrates that coalitions are appropriate vehicles for managing interaction among multiple and diverse organizations. However, as fluid entities without permanent governance systems, coalitions require formalized support mechanisms to function effectively. The value to project designers and policy makers of this paper lies primarily in the description and analysis of the nested" organizational support system which developed to fulfill the every day needs of the coalition in Rajasthan. Its secondary value lies in the discussion of conceptual and practical aspects of building and supporting coalitions.